Pemanfaatan Sampah Spraycan sebagai Katalog Pameran â€œVoice of Wall 6 Hours Exhibitionâ€ - Carollina, Donna (Jurnal Bahasa Rupa, 2017)
The rampant of graffiti activity in Yogyakarta has an impact on increasing the amount of spraycan waste that became the main tools in this activity. The utilization of spraycan waste then becomes an interesting thing, as shown in the street art exhibition catalog â€œVoice of Wall 6 Hours Exhibitionâ€. This exhibition used spraycan waste as a catalog exhibition. Thus this catalog exhibition has been interesting thing to study. This study uses qualitative descriptive method to get a systematic, factual, and accurate description of the utilization of spraycan waste as the exhibition catalog of â€œVoice of Wall 6 Hours Exhibitionâ€.